The contribution of rods and cones to brightness induction - Barrionuevo, Pablo Alejandro (2023)
Retinal mechanisms are involved in the early processing of brightness. However, brightness induction studies that discriminate the contributions of rods and cones at the same light adaptation have been rarely conducted, possibly due to technical limitations. In this study, we assessed isolated rod, isolated cone, and combined rod and cone (LMSR) conditions for contrast and assimilation induction stimuli, using a four-primary projector and the silent substitution method. We generated induction stimuli in mesopic light adaptation with embedded matching and reference patches. Participants had to choose the brighter patch and the induction effect was computed as the normalized difference between the patches’ intensities at the point of subjective equality. For the LMSR condition, contrast and assimilation induction stimuli produced similar responses, and these were significantly higher than responses for a control non-induction stimulus. Similar results were found for the cone condition, although there was a trend for a higher contrast than assimilation effect. For the rod condition, the brightness assimilation effect was significantly higher than brightness contrast. Comparing the three photoreceptor conditions, it became clear that the combined response under mesopic viewing was mostly determined by cones. Therefore, rod-driven brightness induction is notably different from induction obtained in usual photopic or mesopic viewing conditions where cones are involved. We argue that the different behaviour for isolated responses could be explained by asymmetric retinal contrast gain for rods and cones.